Integrate electrical conductivity and Li+ ion mobility into hierarchical heterostructure Ti3C2@CoO/ZnO composites toward high-performance lithium ion storage. (1st December 2020) - Tang, Hong; Jiang, Mengjin; Ren, Erhui; Zhang, Yue; Lai, Xiaoxu; Cui, Ce; Jiang, Shouxiang; Zhou, Mi; Qin, Qin; Guo, Ronghui
Abstract: The structural instability and low electrical conductivity of CoO and ZnO cause their rapid capacity fading when it is used for lithium ion storage, which limits their applications. In response, a hierarchical heterostructure was formed by anchoring CoO/ZnO nanodots onto the surface of Ti3 C2 to effectively address the above issue. Ti3 C2 has an excellent electrochemical performance which can effectively enhance the electrical conductivity of CoO/ZnO and facilitate lithium ion mobility, and CoO/ZnO nanodots that are uniformly anchored on the Ti3 C2 surface can effectively inhibit the aggregation of CoO/ZnO nanodots during cycling. As an anode electrode for lithium-ion batteries, the Ti3 C2 @CoO/ZnO electrode exhibits a high reversible capacity (1069 mA h g −1 at 0.2 A g −1 for over 120 cycles), excellent cycleability (1052 mA h g −1 at 0.5 A g −1 for over 200 cycles, and 627 mA h g −1 at 1 A g −1 for over 300 cycles) and exceptional rate capacity (498 mA h g −1 at 3 A g −1, and holds 794.3 mA h g −1 after 110 cycles when the current is controlled at 0.1 A g −1 again). This work paves the way for the structural modification of other types of metal oxides (sulfides) to enhance electrochemical performance. Highlights: Hierarchical heterostructure Ti3 C2 @CoO/ZnO composites was successfully prepared. CoO/ZnO nanodots uniformly anchored on Ti3 C2 surface. Ti3 C2 can improve the electrical conductivity and lithium ion mobility of CoO/ZnO. High capacity and excellent cycleability at different current densities for LIBs.